(untitled) (Research, Society and Development, 2023)
Introduction: Folliculotropic Mycosis Fungoides (FMF) is the most common case among all variants of Mycosis Fungoides besides Classic Mycosis Fungoides with a worse prognosis than other variants. An understanding of the clinical features and histopathological features of Mycosis Fungoides and its variants is greatly needed in establishing a diagnosis, especially in perspective of Pathology. Methodology: This descriptive study of the case report type and the data obtained from the patient’s medical report. Case Description: A 11 years old girl came with a rash on her right cheek since 3 weeks ago and is increasing in size. On physical examination, there was an erythematous plaque on the right cheek about 2 cm from the nasolabial fold. Microscopic examination showed scattered and infiltrative atypical lymphocyte cells, infiltrative among follicles. The hair follicles showed a degenerated epithelial and cystically dilated epithelium containing follicular mucinosis. Immunohistochemistry shows positive CD3, CD4, CD5, and 10% of Ki67. Conclusion: Although it occurs in 50% of lymphoma cases, cases of Mycosis Fungoides are generally rare. The Folliculotropic Mycosis Fungoides variant is the most common among all the Mycosis Fungoides variants besides Classic Mycosis Fungoides with a worse prognosis than the other variants. It is important to carry out a biopsy examination to assess whether there is an MF lesion, especially Folliculotropic MF in the specimen being examined, moreover if the clinical manifestations in this case vary greatly depending on the stage of the lesion.